Estudo comparativo da arginase em Leishmania (Leishmania) amazonensis, L. (Viannia) braziliensis e L. (L.) infantum - Bárbara Beiral Esteves Santana (2019)
In Brazil, tegumentary leishmaniasis (LT) and visceral leishmaniasis (LV) are endemic and widely distributed, and LT is frequently associated with the species Leishmania (Leishmania) amazonensis and L. (Viannia) braziliensis, whereas the visceral form is caused by L. (L.) Infantum. Clinical forms are determined by parasite and host factors, among which the immune response is highlighted. Arginase and inducible nitric oxide synthase (iNOS) are enzymes that share the same substrate, L-arginine, to produce among other compounds L-ornithine and nitric oxide (NO), respectively. In addition to its role in the formation of important substrates for the proliferation of parasite and host cells, arginase plays a key role in the availability of L-arginine in the cells expressing it, and may contribute to the establishment of Leishmania spp. In this sense, it was our objective to evaluate the abundance and levels of arginase activity in L. amazonensis, L. braziliensis, L. infantum, and also in macrophages infected by these parasites, in addition to correlating with the parasite load. Initially, abundance and arginase activity was determined in each species in promastigote forms. It was observed that L. amazonensis presented 2.6 times greater abundance of arginase when compared to L. braziliensis and L. infantum species. Furthermore, arginase activity levels were also higher in procyclic and metacyclic promastigotes of L. amazonensis when compared to L. braziliensis and L. infantum. Next, we measured arginase activity, NO production and parasite load between macrophages infected by the species studied. No significant difference was observed between levels of enzymatic activity of arginase, NO production or infection rate among macrophages infected by the three species studied. Our data demonstrate that increased abundance and arginase activity in L. amazonensis promastigotes does not influence in vitro macrophage infection.